Influence of Work-Related Stress on the Performance of Teachers in Public Secondary Schools in Kiambu County, Kenya - Lelei, Isaac; Mwangi, Elias; Maina, Justus (Journal of Human Resource and Leadership, 2024)
Purpose: The aim of the study was to influence of work-related stress on the performance of teachers in Public Secondary Schools in Kiambu County, Kenya Methodology: The psychological well-being theory, the person-environment fit theory, and the Job Demands-Resources model served as the guiding theories for the study. The study used a descriptive survey research approach. Target population was 4288 teachers in public high schools out of which a sample size of 365 was selected using Yamane formula. The sample size was chosen using stratified random sampling method. Primary data was collected using questionnaires. To determine the validity and reliability of the questionnaires, a pilot test was carried out. Quantitative analysis of the data gathered from the surveys was conducted. Inferential and descriptive statistics was used for analysis. The data was summarized into frequencies, percentages, means and standard deviation and presented using pie charts and frequency tables. Findings: From the findings, it was established that work related stress (b=0.018, p=0.000<0.05), had a statistically significant relationship with the performance of teachers in public secondary schools in Kiambu County, Kenya. Notably, aspects such as being upset because of things have happened unexpectedly, being unable to control the important things in life, being overwhelmed by the workload significantly affected the performance of teachers in the public secondary schools. Unique Contribution to Theory, Practice and Policy: The study was guided by the person-environment fit theory. The study therefore recommended that the public secondary schools should introduce regular stress management workshops and training for teachers. These programs should focus on coping mechanisms, mindfulness, and relaxation techniques. In order to enhance the environmental mastery of teachers, the school administration needs to offer ongoing professional development opportunities that focus on enhancing adaptability, problem-solving skills, and decision-making abilities.